2022
DOI: 10.3389/fpubh.2022.738634
|View full text |Cite
|
Sign up to set email alerts
|

Family Functioning and Optimism as Protective Factors of Life Satisfaction Among Stroke Patients During the COVID-19 Epidemic in Shenyang, China

Abstract: The coronavirus disease-19 (COVID-19) pandemic may result in detrimental consequences for stroke patient's wellbeing. Family functioning and optimism could help stroke patients cope with crises leading to possible improvements in life satisfaction. This study aims to explore the protective effects of family functioning and optimism on life satisfaction among stroke patients during the COVID-19 pandemic in China. This study was designed as a cross-sectional survey. A total of 207 stroke inpatients who were rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
2
4
1
Order By: Relevance
“…Negative emotions of female university students during the COVID-19 pandemic affect their experiences and goals, while family support can ease anxiety and reduce stress. Also, successful coping experiences and positive emotional experiences can effectively motivate female students to solve problems and achieve goals [43], which is consistent with the Circumplex Model of Family Systems [30], indicating that female students with a sense of belonging to friends, family, and relatives could give themselves a great sense of hope [36]. Our findings indicated that female students' hope could predict their satisfaction with life.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Negative emotions of female university students during the COVID-19 pandemic affect their experiences and goals, while family support can ease anxiety and reduce stress. Also, successful coping experiences and positive emotional experiences can effectively motivate female students to solve problems and achieve goals [43], which is consistent with the Circumplex Model of Family Systems [30], indicating that female students with a sense of belonging to friends, family, and relatives could give themselves a great sense of hope [36]. Our findings indicated that female students' hope could predict their satisfaction with life.…”
Section: Discussionsupporting
confidence: 80%
“…Consistent with Olson’s Circumplex Model of Family Systems [ 30 ] and Broaden-and-Build Theory [ 36 ], the family function may promote life satisfaction via hope, which is considered an enhancing factor. If the degree to which a person regards the quality of interactions among family members (family functioning) as important is higher, their ability to see a desirable outcome as a genuine possibility (hope) is higher [ 42 , 43 ]. In this context, it can be assumed that hope and family functioning protect against negative emotions during the COVID-19 pandemic among female students and improve their life satisfaction [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Negative emotions of university students affect their experiences and goals, and the family support can ease anxiety and reduce stress in these students. Also, successful coping experience and positive emotional experience are effectively motivating to solve problems and achieve goals (42), which is consistent with the Circumplex Model of Family Systems (28), indicating that people with a sense of belonging from friends, family and relatives, were able to present themselves a great sense of hope (35). Our ndings indicated that students' hope could predict their satisfaction with life.…”
Section: Discussionsupporting
confidence: 84%
“…Consistent with Olson's Circumplex Model of Family Systems (28) and Broaden-and-Build Theory (35), family function may promote satisfaction with life via hope which is considered an enhancing factor. The higher the degree to which a person regards quality of interactions among family members (family functioning) as important, their ability to see a desirable outcome as a genuine possibility (hope) is higher (41,42). In this context, it can be assumed that hope and family functioning protect against negative emotions during COVID-19 pandemic and improve life satisfaction (43).…”
Section: Hypothesismentioning
confidence: 99%